Discover how IDNLearn.com can help you find the answers you need quickly and easily. Discover reliable and timely information on any topic from our network of knowledgeable professionals.
Sagot :
To determine which equation has the coefficients [tex]\( a = -2 \)[/tex], [tex]\( b = 1 \)[/tex], and [tex]\( c = 3 \)[/tex], we need to carefully examine each of the given equations and compare them to the general form of a quadratic equation:
[tex]\[ 0 = ax^2 + bx + c \][/tex]
Let's analyze each option one by one:
1. Equation: [tex]\( 0 = -2x^2 + x + 3 \)[/tex]
- Comparing this with the standard form [tex]\( 0 = ax^2 + bx + c \)[/tex]:
- [tex]\( a = -2 \)[/tex]
- [tex]\( b = 1 \)[/tex]
- [tex]\( c = 3 \)[/tex]
This matches the given coefficients exactly: [tex]\( a = -2 \)[/tex], [tex]\( b = 1 \)[/tex], and [tex]\( c = 3 \)[/tex].
2. Equation: [tex]\( 0 = 2x^2 + x + 3 \)[/tex]
- Comparing this with the standard form [tex]\( 0 = ax^2 + bx + c \)[/tex]:
- [tex]\( a = 2 \)[/tex]
- [tex]\( b = 1 \)[/tex]
- [tex]\( c = 3 \)[/tex]
Here, [tex]\( a \neq -2 \)[/tex]. So, this does not match the given coefficients.
3. Equation: [tex]\( 0 = -2x^2 + 3 \)[/tex]
- Comparing this with the standard form [tex]\( 0 = ax^2 + bx + c \)[/tex]:
- [tex]\( a = -2 \)[/tex]
- The term with [tex]\( x \)[/tex] is missing, so [tex]\( b = 0 \)[/tex]
- [tex]\( c = 3 \)[/tex]
Here, [tex]\( b \neq 1 \)[/tex]. So, this does not match the given coefficients.
4. Equation: [tex]\( 0 = 2x^2 - x + 3 \)[/tex]
- Comparing this with the standard form [tex]\( 0 = ax^2 + bx + c \)[/tex]:
- [tex]\( a = 2 \)[/tex]
- [tex]\( b = -1 \)[/tex]
- [tex]\( c = 3 \)[/tex]
Here, neither [tex]\( a \neq -2 \)[/tex] nor [tex]\( b \neq 1 \)[/tex]. So, this does not match the given coefficients.
Upon reviewing all the options, the equation that has an [tex]\( a \)[/tex]-value of -2, a [tex]\( b \)[/tex]-value of 1, and a [tex]\( c \)[/tex]-value of 3 is:
[tex]\[ 0 = -2x^2 + x + 3 \][/tex]
Therefore, the correct equation is:
[tex]\[ 0 = -2x^2 + x + 3 \][/tex]
[tex]\[ 0 = ax^2 + bx + c \][/tex]
Let's analyze each option one by one:
1. Equation: [tex]\( 0 = -2x^2 + x + 3 \)[/tex]
- Comparing this with the standard form [tex]\( 0 = ax^2 + bx + c \)[/tex]:
- [tex]\( a = -2 \)[/tex]
- [tex]\( b = 1 \)[/tex]
- [tex]\( c = 3 \)[/tex]
This matches the given coefficients exactly: [tex]\( a = -2 \)[/tex], [tex]\( b = 1 \)[/tex], and [tex]\( c = 3 \)[/tex].
2. Equation: [tex]\( 0 = 2x^2 + x + 3 \)[/tex]
- Comparing this with the standard form [tex]\( 0 = ax^2 + bx + c \)[/tex]:
- [tex]\( a = 2 \)[/tex]
- [tex]\( b = 1 \)[/tex]
- [tex]\( c = 3 \)[/tex]
Here, [tex]\( a \neq -2 \)[/tex]. So, this does not match the given coefficients.
3. Equation: [tex]\( 0 = -2x^2 + 3 \)[/tex]
- Comparing this with the standard form [tex]\( 0 = ax^2 + bx + c \)[/tex]:
- [tex]\( a = -2 \)[/tex]
- The term with [tex]\( x \)[/tex] is missing, so [tex]\( b = 0 \)[/tex]
- [tex]\( c = 3 \)[/tex]
Here, [tex]\( b \neq 1 \)[/tex]. So, this does not match the given coefficients.
4. Equation: [tex]\( 0 = 2x^2 - x + 3 \)[/tex]
- Comparing this with the standard form [tex]\( 0 = ax^2 + bx + c \)[/tex]:
- [tex]\( a = 2 \)[/tex]
- [tex]\( b = -1 \)[/tex]
- [tex]\( c = 3 \)[/tex]
Here, neither [tex]\( a \neq -2 \)[/tex] nor [tex]\( b \neq 1 \)[/tex]. So, this does not match the given coefficients.
Upon reviewing all the options, the equation that has an [tex]\( a \)[/tex]-value of -2, a [tex]\( b \)[/tex]-value of 1, and a [tex]\( c \)[/tex]-value of 3 is:
[tex]\[ 0 = -2x^2 + x + 3 \][/tex]
Therefore, the correct equation is:
[tex]\[ 0 = -2x^2 + x + 3 \][/tex]
Thank you for joining our conversation. Don't hesitate to return anytime to find answers to your questions. Let's continue sharing knowledge and experiences! Your questions deserve reliable answers. Thanks for visiting IDNLearn.com, and see you again soon for more helpful information.